ANÁLISE COMPARATIVA DAS DIFICULDADES DE ENSINO APRENDIZADO DE CIÊNCIAS NAS ESCOLAS DA ZONA RURAL E ZONA URBANA DO MUNICÍPIO DE BREVES PARÁ - ALMEIDA, Marinete Vilhena (2024)
Learning difficulties typically result from the learning deficit that is expected in relation to other cognitive abilities considered in the age group, therefore this work aims to analyze the difficulties encountered by teachers and students in the process of teaching and learning science in a school in urban areas and another in rural areas in the municipality of Breves Pará. For the theoretical basis, studies by Abreu (2009), Bastos (2013), Bossa (2009), Campos (2010), Cardoso (1977), De Brito (2006), KIRK (1996) among other authors, who emphasize teaching learning difficulties. To understand this process in the school environment, exploratory research was carried out in both schools, using questionnaires with open questions, with students and teachers, qualitative and quantitative methods were also used, in order to collect satisfactory data for the research in question. From the study developed, it is possible to show that the greatest teaching difficulties are related to the physical structure of the school, lack of resources and teaching materials, lack of continued training of teachers, etc. When learning difficulties are associated with the school environment, lack of teaching materials, family life, work, transport, traditional methodologies addressed, etc.